Is craft beer consumption genderless? Exploratory evidence from Italy and Germany. Issue 3 (4th February 2020) - Rivaroli, Sergio; Lindenmeier, Jörg; Spadoni, Roberta
Abstract : Purpose: This study aimed to investigate the gendered nature of craft beer (CB) consumption in Italy and Germany. Design/methodology/approach: Data were collected through online surveys in Italy ( N  = 210) and Germany ( N  = 211). Based on an enhanced version of the theory of planned behaviour, mean value difference tests and moderated regression analyses with gender as a moderator were performed to test gender effects on CB consumption behaviour. Findings: The study results provide evidence that the gap in CB consumption behaviour is not very pronounced. In the German sample, gender did not moderate the effects of the model components on behavioural intent. However, the study found significant mean differences in all model variables. In the Italian sample, gender moderated the effects of several components of the theory of planned behaviour on behavioural intention. Hence, CB consumption appears to represent an opportunity for Italian women to negotiate their womanhood in a historically masculine-dominated space. Research limitations/implications: The limitations of these data are the focus on two specific countries, the use of small-sized samples and the prediction of behavioural intentions instead of actual behaviour. Practical implications: The study may help marketing managers develop appropriate marketing strategies based on a better understanding of gender-specific needs in CB consumption. Originality/value: This investigation provides the first comparative analysis of gender-specific behavioural patterns in CB consumption in two European countries characterised by notably different beer cultures.